2009
DOI: 10.1021/jf900032z
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of Chafurosides A and B in Tea Leaves and Isolation of Prechafurosides A and B from Oolong Tea Leaves

Abstract: A procedure was developed for the quantitative determination of chafuroside A, a flavone C-glycoside with potent anti-inflammatory activity, and its regioisomer chafuroside B, as well as isovitexin and vitexin, by selected reaction monitoring liquid chromatography-tandem mass spectrometry (SRM LC-MS/MS) analysis. This method was successfully applied to commercial leaves of green tea, houji tea, oolong tea, and black tea. High levels of chafurosides A and B were found in oolong tea leaves that had been heated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 21 publications
3
23
0
Order By: Relevance
“…The results of previous work in this area have shown that the extraction of plant material under high temperature conditions such as 160°C can result in high levels of conversion of precursor compounds to the corre- sponding active materials. 22,23) This result therefore suggested that the temperatures used for the microwave irradiation of the tablets in the current study were insufficient to allow for the conversion of the precursors to the corresponding active ingredients. As shown in Fig.…”
Section: Properties Of Odtts Prepared Using Distilled Watermentioning
confidence: 83%
See 3 more Smart Citations
“…The results of previous work in this area have shown that the extraction of plant material under high temperature conditions such as 160°C can result in high levels of conversion of precursor compounds to the corre- sponding active materials. 22,23) This result therefore suggested that the temperatures used for the microwave irradiation of the tablets in the current study were insufficient to allow for the conversion of the precursors to the corresponding active ingredients. As shown in Fig.…”
Section: Properties Of Odtts Prepared Using Distilled Watermentioning
confidence: 83%
“…The supernatant was collected and analyzed by LC-MS/MS (API2000, Agilent, CA, U.S.A.) to determine the amounts of CFA, CFB, Pre CFA and Pre CFB according to the method of previous literature. 23) All of these measurements were repeated three times and the average values were calculated.…”
Section: Characterization Of Odttsmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar approach was used for identification of compound 2 as chrysin-6, 8-di-Cglucoside at a retention time of 2.8 min (Table I) [7]. In negative mode, ESI analysis of compounds 4 and 6 yielded [9]. Vitexin and isovitexin are ubiquitous compounds found in plant kingdom including Scutellaria species [10].…”
Section: Resultsmentioning
confidence: 99%